Primary care physicians' ability to diagnose the most prevalent respiratory diseases - de São José, B P; Camargos, P A M; Bateman, E D; Botelho, C M A; de Seixas Maciel, J G F; Mancuzo, E V; de Amorim Corrêa, R (The international journal of tuberculosis and lung disease, 2016)
There are few reports on the ability of primary care physicians (PCPs) to diagnose acute and chronic respiratory diseases. We assessed the agreement between PCPs and pulmonologists in diagnosing pulmonary tuberculosis (TB), chronic obstructive pulmonary disease (COPD), asthma and acute respiratory infections (ARI). Metropolitan Region of Belo Horizonte, State of Minas Gerais, Brazil. PCPs filled out a symptom-based questionnaire for adult patients presenting with respiratory symptoms. Their diagnoses were compared to those of three pulmonologists who reviewed the data independently without seeing the patients. Agreement between PCP decisions and those of the pulmonologists was assessed. Among a total of 554 patients, 60 PCPs correctly diagnosed 42.4% as having ARI, 17.3% asthma, 15.7% COPD and 12.4% suspected TB. Agreement between the PCPs and the pulmonologists was as follows: 0.53 for asthma (95%CI 0.45-0.60), 0.53 (95%CI 0.46-0.60) for ARI, 0.45 (95%CI 0.34-0.57) for TB and 0.40 (95%CI 0.29-0.50) for COPD. Only reasonable to moderate agreement was found between PCPs and pulmonologists in diagnosing the most prevalent respiratory conditions. This result emphasises the need to adopt measures and provide tools to improve the diagnostic skills of PCPs for patients presenting with respiratory symptoms.